Tropical Plant Species and Technological Interventions for Improvement 2023
DOI: 10.5772/intechopen.104890
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Known African Indigenous Tree and Fruit Plants: Recent Evidence from Literatures and Regular Cultivation Culture

Abstract: Indigenous plant species native to Africa have numerous uses. They have a long and rich ethno-medicinal history with well-known native applications in different African countries. The effects of these indigenous underutilized crops in local traditional medicine differ. But they play an important role in enhancing food and nutrition security of the population. Tropical plant species have economic potential as they make great socio-economic impact on the livelihoods of rural dwellers. Despite their economic, foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 76 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…In terms of fertilizer requirements, studies have shown that soil amendments such as poultry manure are sufficient to promote optimum growth and fruit production of African walnut. Application of 10 t ha −1 of poultry manure is sufficient to complement soil nutrients and enable proper development of morphological traits of the African walnut plant at early stages (Baiyeri and Olajide, 2022). This fertilization requirement supports green and sustainable cultivation of the African walnut plant and reduces the risk of inorganic chemical contamination of the soil and disruption of the soil ecosystem.…”
Section: Sustainability Issues Relating To Production and Utilization...mentioning
confidence: 90%
“…In terms of fertilizer requirements, studies have shown that soil amendments such as poultry manure are sufficient to promote optimum growth and fruit production of African walnut. Application of 10 t ha −1 of poultry manure is sufficient to complement soil nutrients and enable proper development of morphological traits of the African walnut plant at early stages (Baiyeri and Olajide, 2022). This fertilization requirement supports green and sustainable cultivation of the African walnut plant and reduces the risk of inorganic chemical contamination of the soil and disruption of the soil ecosystem.…”
Section: Sustainability Issues Relating To Production and Utilization...mentioning
confidence: 90%
“…In terms of fertilizer requirements, studies have shown that soil amendments such as poultry manure are sufficient to promote optimum growth and fruit production of African walnut. Application of 10 t ha −1 of Frontiers in Sustainable Food Systems 07 frontiersin.org poultry manure is sufficient to complement soil nutrients and enable proper development of morphological traits of the African walnut plant at early stages (Baiyeri and Olajide, 2022). This fertilization requirement supports green and sustainable cultivation of the African walnut plant and reduces the risk of inorganic chemical contamination of the soil and disruption of the soil ecosystem.…”
Section: Sustainability Issues Relating To Production and Utilization...mentioning
confidence: 98%
“…Its potential for food security are embedded in the physicochemical characteristics of the plant and the nuts. African walnut plant is a perennial climber, which currently grows in the wild and utilizes other trees such as the cocoa and kola nut trees as support (Baiyeri and Olajide, 2022). As the plant is perennial, the fruits are produced annually between the months of June and September, thus ensuring the availability of the nuts on a yearly basis.…”
Section: Nutritional Composition and Potential To Improve Nutrition A...mentioning
confidence: 99%
See 2 more Smart Citations